Understanding the Macro-Financial Effects of Household Debt : A Global Perspective - Alter, Adrian; Valckx, Nico.; Xiaochen Feng, Alan. (Washington, D.C. : International Monetary Fund, 2018)
We confirm the negative relationship between household debt and future GDP growth documented in Mian, Sufi, and Verner (2017) for a wider set of countries over the period 1950-2016. Three mutually reinforcing mechanisms help explain this relationship. First, debt overhang impairs household consumption when negative shocks hit. Second, increases in household debt heighten the probability of future banking crises, which significantly disrupts financial intermediation. Third, crash risk may be systematically neglected due to investors' overoptimistic expectations associated with household debt booms. In addition, several institutional factors such as flexible exchange rates, higher financial development and inclusion are found to mitigate this impact. Finally, the tradeoff between financial inclusion and stability nuances downside risks to growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet